ANALYSIS OF THE POTENTIAL FOR IMPLEMENTING THE CONCEPT OF HALAL TOURISM IN WATU KANDANG TOURISM VILLAGE DESTINATIONS, TRENGGALEK DISTRICT - Permana, Dhiam; Qadariyah, Lailatul (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2023)
This research discusses the analysis of the potential for implementing the halal tourism concept at the Watu Kandang Tourism Village destination in Trenggalek Regency. Watu Kandang Tourism Village is a new tourist destination that focuses on ecotourism and offers direct interaction with nature and the lives of local people. This research aims to analyse the potential for implementing the halal tourism concept in the Watu Kandang Tourism Village based on halal tourism criteria according to the Global Muslim Travel Index. The research method used is qualitative, with data collection techniques through interviews, observation, and documentation. Data were analysed through data reduction, data presentation, and drawing conclusions. The research results show that the Watu Kandang Tourism Village has good potential to be developed into a halal tourist destination. This can be seen from the criteria for halal tourism that are fully in place in the Watu Kendang tourist attraction. Apart from that, this tourism is supported by easy accessibility to the location, adequate worship and toilet facilities, a beautiful and safe environment, as well as food and drinks that guarantee halal. So according to the criteria above, Watu Kendang tourism is worthy of being used as a halal tourist destination in Indonesia.